2007
DOI: 10.3174/ajnr.a0563
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Hemangiomas: Various Types of MR Imaging Features with Histopathologic Correlation

Abstract: BACKGROUND AND PURPOSE:Because of the high vascularization of hemangiomas, preoperative misinterpretation may result in unexpected intraoperative hemorrhage and incomplete resection, which results in the persistence of clinical symptoms or recurrence. Our purpose was to analyze various MR imaging features of a spinal epidural hemangioma with histopathologic correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 15 publications
0
73
0
2
Order By: Relevance
“…Preoperative MRI is necessary for accurate diagnosis of spinal epidural CM [1,9,14,18]. These lesions tend to display iso-signal or low signal on T1WI and high signal on T2WI, with homogeneous enhancement after injection of contrast material, most of which are located in the posterior epidural space and present with myelopathy [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative MRI is necessary for accurate diagnosis of spinal epidural CM [1,9,14,18]. These lesions tend to display iso-signal or low signal on T1WI and high signal on T2WI, with homogeneous enhancement after injection of contrast material, most of which are located in the posterior epidural space and present with myelopathy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Morioka et al proposed to differentiate these tumors and spinal CM by enlargement of intervertebral foramina, suggesting that the latter is rarely likely to cause dilation compared to the former [6]. Conversely, this proposal is contradicted by Lee et al, who found that CM usually leads to a neural foraminal widening [18]. These lesions not only show dilated intervertebral foramina, but also tend to invade the vertebral body, and pedicle of vertebral arch, with heterogeneous enhancement and enhance less than spinal CMs and usually with cystic changes, which is different from spinal epidural CMs.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate diagnosis depends on pathology. Histologically, CAs must be distinguished from arteriovenous malformations and capillary hemangiomas (27,28). The arteriovenous malformation shows with a cluster of abnormal arteries and veins and vessel walls containing elastin, and smooth muscle (28).…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, CAs must be distinguished from arteriovenous malformations and capillary hemangiomas (27,28). The arteriovenous malformation shows with a cluster of abnormal arteries and veins and vessel walls containing elastin, and smooth muscle (28). The characteristic features of capillary hemangioma are thin irregular capillary-sized vessels caught in low attenuating fibroses, lobular architecture and the presence of a lining of a continuous basal lamina (29).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these dynamic CT findings, a diagnosis of hepatic hemangioma was established. 8,9) A T3 to T4 laminectomy was performed. Complete decompression of the spinal cord with meticulous hemostasis using bone wax was achieved.…”
Section: Case Reportmentioning
confidence: 99%